Aravind Adiga’s Novel on Caste and Religion: - (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This research explores the manifestation of social realism and the reflection of globalizationwithin the selected novels of Aravind Adiga, a prominent contemporary Indian author. Adiga's works,known for their incisive critique of societal issues, provide a lens through which the impact ofglobalization on individuals and communities can be analyzed. This study investigates how Adiga'snovels capture the complexities of a rapidly changing world while depicting the challenges andinequalities brought about by globalization. The Man Booker Prize-winning novel the White Tiger (2008),the short-story collection Between the Assassinations (2009), Last Man in the Tower (2011), and the mostrecent novel Selection Day (2016) are all works of fiction by Aravind Adiga, who was born on October 23,1974, in Madras (now Chennai), India. Despite India's steady march to global superpower status, theWhite Tiger explores the irony of how the subaltern people are still being oppressed and exploited by theprivileged class of the society.Adiga's second book, Between the Assassinations, is a collection of twelve connected short tales thatfocus on various social and religious groups in India. The male protagonists of the third book Last Manin Tower are middle-class guys trying to make a name for themselves in the glistening Mumbai propertymarket. Adiga portrays Mumbai, India, in this book as a thriving financial and commercial center offeringa wide range of possibilities.